Sudden unexpected death in epilepsy genetics: Molecular diagnostics and prevention - Goldman, Alica M. (Epilepsia, 2016)
Epidemiologic studies clearly document the public health burden of sudden unexpected death in epilepsy (SUDEP). Clinical and experimental studies have uncovered dynamic cardiorespiratory dysfunction, both interictally and at the time of sudden death due to epilepsy. Genetic analyses in humans and in model systems have facilitated our current molecular understanding of SUDEP. Many discoveries have been informed by progress in the field of sudden cardiac death and sudden infant death syndrome. It is becoming apparent that SUDEP genomic complexity parallels that of sudden cardiac death, and that there is a pauci1ty of analytically useful postmortem material. Because many challenges remain, future progress in SUDEP research, molecular diagnostics, and prevention rests in international, collaborative, and transdisciplinary dialogue in human and experimental translational research of sudden death.